Management of leaf spot caused by Alternaria alternata in gerbera through chemicals - Mazumder, N; Borah, S K; Hatibarua, Preeti (Indian Journal of Plant Protection, 2020)
The efficacy of six fungicides viz., mancozeb (0.2%), propineb (0.2%), carbendazim (0.2%) iprodione (25%) + carbendazim (25%) (0.2%), difenoconazole (0.05%) and azoxystrobin (0.1%) were evaluated for managing leaf spot of gerbera (Gerbera jamesonii Hook) var. Red Gem during rabi seasons of 2013-16. Four sprays with difenoconazole (0.1%) and a combination fungicide consisting of iprodione (25%) + carbendazim (25%) (0.2%), each one at seven days interval (with the first spray at the onset of the disease)was the most effective and resulted in the lowest per cent disease incidence of 16.50 and 20.30%, respectively compared to control (53.68%). Economic analyses also revealed effectiveness of difenconazole and iprodione + carbendazim which recorded highest B:C ratios of 4.50 and 4.41 with 68.27% and 61.70% disease reduction, respectively.